ORGANOLEPTIC EVALUATION OF FORTIFIED CHICKEN SAUSAGE WITH LIQUID SMOKE AT DIFFERENT CONCENTRATIONS - I G. A. D. A., Astawa; Miwada, I N. S.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aims to determine the effect of liquid smoke fortification with different concentrations in the dough on the organoleptic quality of chicken sausages. This study used a completely randomized design (CRD) with 5 treatments and 4 replications assessed by 25 semi-trained panelists. The data obtained were analyzed using the Non-Parametric Kruskal Wallis analysis, if there was a significant difference between the treatments (P<0.05) then it was continued with the Mann Whitney test with the help of the SPSS 25 program. The five treatments given were: liquid smoke fortification with a concentration of 0% mixture as a control (P0), liquid smoke fortification with a concentration of 0.2% mixture (P1), liquid smoke fortification with a concentration of 0.4% mixture (P2), liquid smoke fortification with a concentration 0.6% mixture (P3), and liquid smoke fortification with a concentration of 0.8% mixture (P4). The variables observed were organoleptic evaluation including color, aroma, taste, texture, and overall acceptance. The results showed that the fortification of liquid smoke in chicken sausages was significantly different (P<0.05) in color, aroma, texture and overall acceptability, while the taste was not significantly different (P>0.05). The conclusion of this study is that liquid smoke fortification in chicken sausages can improve the organoleptic quality of chicken sausages in terms of color, aroma, texture, and overall acceptability, but does not affect the taste of chicken sausages. Fortification of liquid smoke at a concentration of 0.8% of the mixture produced chicken sausages with the best organoleptic quality and was preferred by panelists with hedonic quality criteria including chicken sausages that are slightly dark in color, smell of smoke, have a non-bitter taste, and have a chewy texture.